Digestive Malacoplakia in Children: Case Report. (20th December 2010) - Bouguila, J.; Brahim, K.; Mokni, M.; Skandrani, K.; Harbi, A.; Essoussi, A. S.; Boughammoura, L.
Abstract : Malacoplakia is a form of chronic granulomatous inflammatory reaction that rarely affects the pediatric age group. The gastrointestinal system is the second most common site for the occurrence of malacoplakia. We report the case of a 9-year-old girl who was hospitalized for abdominal pain, chronic diarrhea, and rectal hemorrhage. The endoscopic examinations and histopathology confirmed the diagnosis of intestinal malacoplakia. We successfully treated her with oral levofloxacin. This disease does not have any specific clinical or biological signs, and the diagnosis is exclusively based on histology.